2022
DOI: 10.1001/jamainternmed.2021.6373
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Antenatal Diet and Physical Activity–Based Interventions With Gestational Weight Gain and Pregnancy Outcomes

Abstract: IMPORTANCE Excessive gestational weight gain (GWG) is common and associated with adverse pregnancy outcomes. Antenatal lifestyle interventions limit GWG; yet benefits of different intervention types and specific maternal and neonatal outcomes are unclear. OBJECTIVE To evaluate the association of different types of diet and physical activity-based antenatal lifestyle interventions with GWG and maternal and neonatal outcomes.DATA SOURCES A 2-stage systematic literature search of MEDLINE, Embase, Cochrane Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
0
11

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 161 publications
(196 citation statements)
references
References 70 publications
7
178
0
11
Order By: Relevance
“…Importantly, pregnancy is a time when women are more motivated to improve their health behaviors. [47] Of note, our data suggest that adherence to the 2009 NAM weight gain recommendations can be helpful in reducing risk of adverse outcomes among low-risk pregnant women. Thus, adequate training of clinicians to effectively counsel these women on achieving healthy weight gain targets appears mandatory.…”
Section: Discussionmentioning
confidence: 73%
“…Importantly, pregnancy is a time when women are more motivated to improve their health behaviors. [47] Of note, our data suggest that adherence to the 2009 NAM weight gain recommendations can be helpful in reducing risk of adverse outcomes among low-risk pregnant women. Thus, adequate training of clinicians to effectively counsel these women on achieving healthy weight gain targets appears mandatory.…”
Section: Discussionmentioning
confidence: 73%
“…Recent systematic reviews of randomised controlled trials (RCTs) of diet and physical activity during pregnancy (N range: 12,526-34,546) reported some evidence of reduced risk of GDM, LGA, caesarean section in those randomised to the intervention, but no effect or mixed results of the intervention on HDP, PTB, NICU admission. 4345 Of note, these studies aimed at managing weight gain during pregnancy rather than targeting weight reduction prior to pregnancy with a modest mean difference of −0.7 to −1.2 kg between women in the intervention compared to those randomised to standard care. In addition, evidence for many outcomes is uncertain due to the relatively small number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal pre-existing obesity is a modifiable risk factor and represents an important opportunity for dietary and physical activity interventions at the preconception or early pregnancy stages. The risk of GDM and HDP may be partially mitigated through healthy lifestyle in pregnancy and limiting excessive GWG, based on a systematic review and meta-analysis of 117 randomised controlled trials with over 34,000 women [85]. Identifying those at high risk of metabolic complications enables targeted prevention before, during and beyond pregnancy.…”
Section: Implications For Clinical Practice and Future Researchmentioning
confidence: 99%